Kafa’ah Nasab Sebagai Syarat Utama Bagi Pernikahan Wanita Syarifah di Kecamatan Lau - Said Syaripuddin; Andi Banna (Al-Tafaqquh: Journal of Islamic Law, 2022)
This study seeks to reveal the attitude of the syarifah women's community in Lau sub-district, which sets specific criteria in selecting their prospective husbands in the form of kinship equivalence. The principle of lineage kafa'ah in marriage is still being maintained to this day. This study uses a qualitative-descriptive type and approach. Data collection was done by interview and observation. Data analysis in this study took place simultaneously with the data collection process. Data analysis was carried out through three stages of the water model, namely data reduction, presentation, and data verification. However, these three stages take place simultaneously, with the aim of presenting accurate data and information in the context of increasing public understanding and awareness of marriage kafa'ah in accordance with the spirit of Islamic religious provisions. The results found that the attitude of the community of Syarifah women in Lau sub-district who still firmly maintain the principle of kafa'ah nasab in their marriage cannot be separated from their belief that kafa'ah nasab in marriage is a condition that can guarantee their household in harmony. Second: social culture. They consider that the principle of kafa'ah nasab in choosing a prospective husband is a prestige in building a household.